A Modern Mourning Ritual in Iranian Theater: The City of Tales - Seval Günbal Bozkurt (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
This study addresses the life and works of Bijan Mofid, who interpreted Iranian folk literature and culture in theater works with a unique style, and examine his work The City of Tales in terms of style and content. The City of Tales is the author’s masterpiece and was put on stage many times in Iranian theaters, in addition to being adapted for both radio play and the cinema in later years. In The City of Tales, Mofid benefited as much as possible from different types of traditional Iranian siyah-bazi theater and such forms as puppet plays and elegy recitation from the condolence culture. The author blended traditional forms with a modern language in his plays, which included an interpretation that could be called a first in modern Iranian theater in this sense. Although The City of Tales is shown among children’s plays, it is a drama full of satire, for the play is a lament for modern humans who have become alienated from themself and lost their identity. The City of Tales is an allegorical play that emphasizes the process of gaining status in society to be at the cost of losing one’s inherent characteristics, people’s struggle to prove their identity/personality, and estrangement from the self at the end of this struggle.